THE RELATIONSHIP BETWEEN PEER EMOTIONAL SUPPORT AND BURNOUT IN STUDENTS : LITERATURE REVIEW - Rafi Dwi Kusuma; Indri Heri Susanti; Wilis Sukmaningtyas (Bajang Institute, 2022)
Unrelenting and persistent pressure will cause bad effects such as burnout and changes in self-motivation. Some of the effects of burnout on student include the lecture process becoming less effective, such as reraly doing assignment, depression, cheating and irregular sleep patterns. Emotional support in one form of support provided. This study was conducted whit the aim of knowing the description betweeb peer emotional support and burnout in students : Literature Review. The method used in this study is a literature review research method. Objectivity, authenticity of writing and contributions to research are things that mush be considered in the selection of data sources. In this research, the method used is secondary research methodology in the from of Literature Review whit primary source. The PICO (Population, Intervention, Compare, Outcame) approach is an extraction method used in the data collection process. Based on a review of 8 journals that have been reviewed, the results show that thet most influential support is social support. Social support is the support received by aperson from certain individuals who are in his life and are in a certain social environment, this support consists of support for nonverbal and verbal advice or informations, real assistance provided bu other individuals where this social support refers to actions what other individuals do when they ask for help. The higher the social support from peers, the lower the student experience with burnout, and conversely the less social support, the higher the student experience with burnout